Penjatuhan Hukuman Bagi Pelaku Golput sebagai Upaya Mendorong Partisipasi Publik dalam Pemilu yang Harmonis - Rizki Maulana Syafei; Ikram Ibrahim; Nabila Rizq Wildanbati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research examines the problem of law enforcement against abstention behavior in elections in Indonesia, with a focus on punishment for abstention behavior that does not vote and does not come to the polling station. The background of this research is the legal vacuum arising from the current election law enforcement system, which is characterized by the ups and downs of the abstention rate that occurs. In 2004 the abstention rate amounted to 20.24%, in 2009 the number of abstentions increased to 25.19%, in 2014 the number of abstentions increased more drastically to 30, 22%, while the last in 2019 the number of abstentions decreased to 18.03%. The purpose of this research is to evaluate the implications of abstention on democratic development and to provide sanctions regulations in the form of administrative and criminal sanctions for abstainers who do not come to the polling stations. The research method used is descriptive qualitative analysis, by examining relevant primary and secondary data. Data was collected through literature study, and analysis of related documents. The results of this study show that abstention is an act that is not allowed by a country. Abstention behavior can reduce the level of election participation and the level of legitimacy as a prerequisite for the state as a democracy. Thus, it is necessary to reform the regulations under citizens who abstain from coming to the polling stations must be subject to punishment in the form of both administrative sanctions and criminal sanctions which will be related to policies submitted to the legislators.